RELATIONSHIP HUSBAND SUPPORT OF ANEMIA MANAGEMENT WITH INCIDENCE ANEMIA IN PREGNANCY - noer saudah; Heni Frilasari; Candra Reta; Yulianto Yulianto (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Anemia during pregnancy caused death in the mother and fetus. Husband's support for reduction the risk of anemia during pregnancy was important. The purpose study was to determine relationship husband's support of anemia management with the incidence anemia in pregnant. Design research used analytic correlation with a cross-sectional. The population were third trimesters pregnantcy in Mojokerto City. Sample size were 54 pregnant women with purposive sampling. Independent variabel was husband support. Dependent variabel was anemia in pregnant. Instrument used a questionnaire and Analyse data with spearman rank test. Results showed the majority had positive support and not anemia, namely 24 respondents (44.4%) while mild support and mild anemia were 15 respondents (25.9%). Spearman rank test p = 0.0002 and correlation coefficient 0.838. It’s means the relationship between two variables is significant. The correlation between the relationship of husband support with anemic events in pregnant women and the nature of one-way relationships. There is a significant and very strong relationship. Husbands who are able to provide positive support to pregnant women can reduce the risk of anemia during pregnancy. The husband must provide support to wife including giving attention, empathetic, advice, knowledge so that the risk of anemia in pregnancy decreases